Review Artikel: Karakterisasi Dan Uji Efektivitas Antikanker Nanopartikel Emas (AuNPs) Dan Nanopartikel Perak (AgNPs) Dengan Ekstrak Kunyit (Curcuma spp.) Sebagai Bioreduktor - Haura, Izmi; Mulki, Munir Alinu (Journal of Pharmaceutical and Sciences, 2025)
Cancer is one of the leading causes of death in the world with major challenges in the form of therapeutic side effects, poor selectivity, and drug resistance. Nanotechnology, particularly the use of gold (AuNPs) and silver (AgNPs) nanoparticles, offers a promising alternative to improve the effectiveness of cancer therapy. This article reviews recent developments in the synthesis of AuNPs and AgNPs using turmeric as a natural, environmentally friendly bioreductor. Characterization of nanoparticles through UV-Vis, TEM, SEM, and FT-IR methods showed particle sizes ranging from 1-100 nm, spherical or hexagonal morphology, and the presence of functional groups such as -OH and C=O that support stability and bioactivity. Anticancer studies show that these nanoparticles are effective against various types of cancer cells, including breast (MCF-7, MDA-MB-231), lung (A549, NCI-H661, NCI-H1975, NCI-H1573, NCI-H1563), cervical (HeLa), and epithelial (Hep-2) cancers.